PELATIHAN PEMANFAATAN APLIKASI SEBAGAI PERANGKAT ASSESMEN BAGI GURU TAMAN KANAK-KANAK ISLAM QOLBU INSANI DEPOK - Siti Marti’ah; Berta Dian Theodora (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The implementation of PAUDDIKDASMEN learning during the COVID-19 pandemic was carried out with limited face-to-face learning and distance learning. Teachers face problems including the effectiveness of learning tools, especially on indicators of student involvement in the implementation of learning with planning sub-indicators. The training activities carried out with the teachers and kindergarten staff who were participants went well, the participants were very enthusiastic about receiving new knowledge about assessment methods using applications that could be used and utilized during limited face-to-face learning and distance learning. The conclusions from this activity include: 1) Participants gain knowledge about assessment methods that can be used during limited face-to-face learning and distance learning. 2) Participants gain knowledge about applications that can be used for assessment during limited face-to-face learning and distance learning.